The Impact of Accounting Information Systems on Organizational Performance: The Context of Saudi’s SMEs - Trabulsi, Rehab U. (International Review of Management and Marketing, 2018)
Accounting Information System (AIS) is considered as an important organizational mechanism that is critical for the effectiveness of decision making and control in organizations. The main purpose of this paper is to investigate the impact of AIS on organizational performance (cost reduction, improving quality and effective decision making). Data is collected through questionnaires from SMEs in Saudi Arabia. SmartPLS was used to analyze the data and to test the study hypotheses. Findings proof that using an AIS has a significant impact on organizational performance generally and on all its dimensions including cost reduction, improving quality and effective decision making. Keywords: Accounting information system, organizational performance, quality, decision making. JEL Classifications: M40; M41